Estimation of genetic parameters of important economic traits in Aseel chicken: Economic traits in Aseel chicken - Pallavi Rathi; Devender Singh Dalal; Chandrashekhar Santosh Patil (Indian Journal of Poultry Science, 2025)
The data pertaining to 529 Aseel birds across three generations (2018-19 to 2020-21), maintained at the Poultry Breeding Farm of the Department of Animal Genetics and Breeding at LUVAS, Hisar, were used to estimate genetic parameters of important traits. A mixed linear model was employed for the analysis, incorporating sire as a random effect and generation and hatch as fixed effects. The performance traits including age at first egg (AFE), body weight at 20 weeks of age(BW20),body weight at 40 weeks of age(BW40),egg number up to 40 weeks (EN40),egg weight at 40 weeks(EW40)egg mass at 40 weeks of age(EM40). Highly significant (P≤0.01) effect of generation was observed on all traits except EM40.The least squares means for performance traits AFE,BW20,BW40,EN40,EW40, EM40were 175.37±0.71 days,1198.03±7.91 g, 1674.62±7.01g, 67.78±0.77 eggs,46.71±0.14 g, and 2893.82± 54.06 g, respectively. The heritability estimates were moderate to high for all the traits. The age at first egg(AFE) was negatively correlated with egg weight at 40 weeks(EW40) of age and egg mass at 40 weeks of age (EM40).Body weight at 20 weeks of age(BW20) had strong association with EW40. Moderate to high estimates of heritability for performance traits indicated that these traits can be improved through family selection.